INCP procedures in a patient with lung cancer - Gdowska, Kinga; Mess, Eleonora (Journal of Education, Health and Sport, 2022)
Lung cancer is the most common malignant tumour in Poland and the first cause of death among oncological diseases. This article presents the main factors causing lung cancer, the course of the disease and health consequences. The most important nursing problems have been identified, taking into account the individual nursing plan. Nursing actions were proposed to adapt the patient to the new situation, to improve his physical and psychological condition and to educate the patient and his family.